Handbook of type 1 diabetes mellitus : etiology, diagnosis, and treatment - Aucoin, Leon; Prideux, Tristan (New York : Nova Biomedical Books, 2010)
Type I diabetes (T1D) is an autoimmune, and inflammatory disease. This book reviews and discusses the progress on environmental triggers and endogenous alarmins linking innate immunity to the pathogenesis of type 1 diabetes. It also examines the potential anti-inflammatory treatments for T1D evaluated in several models of the disease
1. Environmental factors and concepts in the induction of type 1 diabetes -- 2. Novel approaches for the treatment of type 1 diabetes (T1D) : lessons from murine models -- 3. Nonconventional variability analysis of cardiovascular signals in diabetes mellitus : a new tool to detect autonomic neuropathy -- 4. AMPK-S6K1 signaling pathway as a target for treating hepatic insulin resistance -- 5. Environmental triggers and endogenous alarmins linking innate immunity to the pathogenesis of type 1 diabetes -- 6. Vaccines for type 1 diabetes -- 7. A genetic diagnosis to type 1 diabetes? -- 8. Long-chain polyunsaturated fatty acid supply in diabetes mellitus -- 9. Insulin resistance and nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH) -- 10. The role of physical activity in the treatment of type 1 diabetes mellitus -- 11. Body composition and type 1 diabetes -- 12. Management of type 1 diabetes mellitus in children -- 13. Autoimmune disorders associated with type 1 diabetes mellitus : diagnosis and implications for diabetes control -- 14. Diabetes mellitus : a disease of neglect and business enterprise -- 15. Hope and challenges for islet transplantation in the treatment of type 1 diabetes -- 16. Insulin resistance and polycystic ovary syndrome -- 17. Zn2+-transporter-8 : a dual role in diabetes -- 18. Changes in the diabetic retinopathy in type 1 diabetic patients, after 14 years in a Spanish population, after the new diabetes mellitus diagnosis criteria and a more strict control of the patients -- 19. The dilemmas in differential diagnosis of types of diabetes in adolescent patients -- 20. Insulin resistance in Alzheimer disease -- 21. Efficacy of phytotherapeutical products (Eridiarom, Ddiavit) in treatment of type 1 diabetes mellitus -- 22. New paradigm : on the road to prevent type 1 diabetes -- 23. Type 1 diabetes mellitus and autoimmune gastritis -- 24. Function of the hypothalamic-pituitary-adrenal axis in patients with comorbidity of depression and diabetes : a clinical control study
Includes bibliographical references and index
Keywords: Diabetes